Comparative Reliability of a Novel Electromechanical Device and Handheld Ruler for Measuring First Ray Mobility. (December 2021) - Morgan, Oliver J.; Hillstrom, Rajshree; Turner, Robert; Day, Jonathan; Thaqi, Ibadet; Caolo, Kristin; Song, Jinsup; Russell, Roland; Ellis, Scott; Deland, Jonathan T.; Hillstrom, Howard J.
Background: Quantifying first ray mobility is crucial to understand aberrant foot biomechanics. A novel device (MAP1 st ) that can perform measurements of first ray mobility in different weightbearing conditions, foot alignments, and normalization was tested. The reliability of these measurement techniques was assessed in comparison to a handheld ruler considered representative of the common clinical examination. Methods: The study included 25 participants (50 feet). Two independent raters performed baseline, test-retest, and remove-replace measurements of first ray mobility with MAP1 st and the handheld device. The effects of non-, partial, and full weightbearing in subtalar joint neutral and the resting calcaneal stance position were assessed. Measurement normalization relative to foot size was also investigated. Intra- and interclass correlation coefficients (ICCs) were calculated for each device between the 2 raters. In addition, Bland-Altman plots were constructed to determine if fixed biases or substantial outliers were present. Results: Similar intrarater ICC values were found for both devices (≥0.85). However, interrater ICC values were substantially improved by MAP1 st compared with the handheld device (0.58 vs 0.06). Bland-Altman plots demonstrated biases of 1.27 mm for the handheld ruler, and 2.88 to 0.05 mm and −1.16 to 0.00 for linear and normalized MAP1 st measurements, respectively. Improved reliability was achieved with MAP1 st for normalized assessments of first ray mobility while the foot was placed in partial- and full-weightbearing resting calcaneal stance positions. Conclusion: MAP1 st provided reliable assessments of partial- and full-weightbearing first ray mobility. It should help investigators to explore the potential relationships between first ray function and aberrant foot biomechanics in future research. Level of Evidence: Level II, prospective cohort study.